Immunobinding‐induced alteration in the electrophoretic mobility of proteins: An approach to studying the preconcentration of an acidic protein under cationic isotachophoresis. Issue 9 (7th February 2019) - Guo, Shuang; Jacroux, Thomas; Ivory, Cornelius F.; Li, Lei; Dong, Wen‐Ji
Abstract: The objective of this study is to explore an approach for analyzing negatively charged proteins using paper‐based cationic ITP. The rationale of electrophoretic focusing the target protein with negative charges under unfavorable cationic ITP condition is to modify the electrophoretic mobility of the target protein through antigen‐antibody immunobinding. Cationic ITP was performed on a paper‐based analytical device that was fabricated using fiberglass paper. The paper matrix was modified with (3‐aminopropyl)trimethoxysilane to minimize sample attraction to the surface for cationic ITP. Negatively charged BSA was used as the model target protein for the cationic ITP experiments. No electrophoretic mobility was observed for BSA‐only samples during cationic ITP experimental condition. However, the presence of a primary antibody to BSA significantly improved the electrokinetic behavior of the target protein. Adding a secondary antibody conjugated with amine‐rich quantum dots to the sample further facilitated the concentrating effect of ITP, reduced experiment time, and elevated the stacking ratio. Under our optimized experimental conditions, the cationic ITP‐based paper device electrophoretically stacked 94% of loaded BSA in less than 7 min. Our results demonstrate that the technique has a broad potential for rapid and cost‐effective isotachphoretic analysis of multiplex protein biomarkers in serum samples at the point of care.